The impact of decreased SIRT1 levels on pediatric primary hypertension and left ventricular hypertrophy: a case-control study - Yuting Wang; Yao Lin; Hui Wang; Yaqi Li; Chen Shen; Lin Shi (BMC Pediatrics)
Abstract Background Decreased SIRT1 exhibits a correlation with a range of cardiovascular diseases. However, the changes in serum SIRT1 levels in pediatric primary hypertension have not been reported. This study aimed to investigate serum SIRT1 levels in pediatric primary hypertension and explore its association with left ventricular hypertrophy in the context of hypertension. Methods 126 participants were recruited and categorized into the hypertensive group and the control group. Serum SIRT1 levels were comparatively investigated. Spearman correlation was utilized to establish an association between SIRT1 and blood pressure. Additionally, SIRT1 levels were comparative analyzed between the patients with and without left ventricular hypertrophy. Results The case group had markedly decreased SIRT1 levels than the control group (p < 0.001), and a negative association between SIRT1 levels and blood pressure was revealed (p < 0.01). In subgroup analysis, patients with left ventricular hypertrophy exhibited notably reduced SIRT1 levels (p = 0.011). The multivariate logistic regression analysis showed that lower serum SIRT1 level was an independent risk factor for hypertension (OR = 0.447, 95% CI: 0.269–0.743, p = 0.002) and left ventricular hypertrophy (OR = 0.639, 95% CI: 0.486–0.840, p = 0.001). Conclusions Serum SIRT1 levels were significantly lower in pediatric primary hypertension patients and were negatively correlated with blood pressure. Patients with left ventricular hypertrophy had significantly lower serum SIRT1 levels, and decreased serum SIRT1 was an independent risk factor for left ventricular hypertrophy.